Pengaruh Perceived Credibility, Perceived Reputation, dan Brand Trust terhadap Brand Loyalty pada Pengguna Smartphone - Prayogo, Muhammad Aditya; Setyawan, Anton Agus (Journal of Economics Business Finance and Accounting, 2023)
Changes that occur in the technology and economic sectors have an impact on individual jobs and careers, making it important to analyze the factors that influence career success. This study aims to analyze the effect of Perceived Credibility, Perceived Reputation, and Brand Trust on Brand loyalty (OPPO smartphone research study. The study used a sample of 100 student respondents at UIN Raden Mas Said Surakarta). The data collection method in this study is the questionnaire method. As for the data analysis method used is SEM-PLS analysis with the help of SmartPLS 3. The results show that partially perceived credibility, perceived credibility, and reputation has a positive and significant effect on brand loyalty. Partially brand trust and perceived credibility has a positive and significant effect on band trust. Brand loyalty has a positive and significant effect on brand trust, perceived credibility has a significant positive effect on brand loyalty through brand trust, and perceived reputation has a positive and significant effect on brand loyalty through brand trust.